Clinical and Molecular Study of NPC in Iran: Report of 5 Novel Mutations - TONEKABONI, Seyed Hassan; ARYANI, Omid; KARIMZADEH, Parvaneh; ZAMAN, Talieh; ASHRAFI, Mahmoud Reza; SALEHPOUR, Shadab; DEHGHAN MANSHADI, Masoumeh; KHALILI E, Elham; HOUSHMAND, Masoud (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Tonekaboni SH, Aryani O, Karimzadeh P, Zaman T, Ashrafi M, Salehpour Sh, Dehghan Manshadi M, Khalili E, Houshmand M. Clinical and Molecular Study of NPC in Iran: Report of 5 Novel Mutations. Ir an J Child Neurol. 2015 Autumn;9:4(Suppl.1): 8-9. Pls see pdf.